Influence of ovarian torsion on reproductive outcomes and mode of delivery - Silberstein, Tali; Freud, Amir; Baumfeld, Yael; Sheiner, Eyal; Weintraub, Adi Yehuda; Mastrolia, Salvatore Andrea; Trojano, Giuseppe; Bernstein, Eli Harris; Schwarzman, Polina (Frontiers in Medicine, 2024)
Purpose: To investigate differences in reproductive outcomes among patients before and following ovarian torsion.In this retrospective cohort study, we investigated the reproductive outcomes of patients who underwent surgery for ovarian torsion between 1988-2015 in a tertiary medical center. Data on deliveries before and after ovarian torsion were compared.Results: During the study period, 199 women underwent surgery due to ovarian torsion. The majority (91.4%; n=182) underwent detorsion, and 8.6% (n=17) underwent unilateral adnexectomy. At the time of the torsion, 27.6% (n=55) of patients were pregnant. Among women who suffered from ovarian torsion, about half (52%) of the deliveries occurred before the torsion and 48% following the torsion. No significant difference in the live birth rate was noted (p=0.19). The fertility treatment rate in our cohort was 7.5% before and 5% after the torsion (p=0.01). In addition, live birth, cesarean delivery, and fertility treatment rates were similar in women who underwent the detorsion vs. those who had adnexectomy.Surgically treated ovarian torsion does not appear to negatively influence fertility and live birth potential.